(untitled) (Colombia Medica, 1990)
New strategies for high-risk assessment have been developed around the world in recent years in response to the increasing pressure for health services of good quality and extended coverage. International agencies like WHO, UNICEF, and the governments emphasize the need for local models based on geographically defined areas and built up with community involvement. This paper summarizes recent experiences from the Municipal Health Service of Cali, Colombia, where the so-called "SILOS" (Sistemas Locales de Salud) or Local Health Systems model has been successfully worked out.